IoT, Big Data and AI for Improving Quality of Everyday Life: Present and Future Challenges IOT, Data Science and Artificial Intelligence Technologies - Singh, Pradeep Kumar; Wierzchoń, Sławomir T.; Pawłowski, Wiesław; Kar, Arpan Kumar; Kumar, Yugal (Studies in Computational Intelligence, 2023)
XI, 391 p. 128 illus., 106 illus. in color.